Use of blinatumomab and CAR T-cell therapy in children with relapsed/refractory leukemia: A case series study - Songmi Wang; Aiguo Liu; Na Wang; Yaqin Wang; Ai Zhang; Li Wang; Wen Yu; Chunrui Li; Yicheng Zhang; Qun Hu (Frontiers Media S.A., 2023)
BackgroundThe 5-year event-free survival rate for childhood acute lymphoblastic leukemia (ALL) has increased to more than 85%. However, the 5-year overall survival rate in children with relapsed/refractory ALL did not exceed 50%. In the past decade, immunotherapies (such as blinatumomab and chimeric antigen receptor T-cell therapy) were approved for relapsed/refractory B-ALL, transforming the treatment environment for children with relapsed/refractory ALL.ObjectiveThis study aimed to explore how immunotherapy can be incorporated into salvage regimens for pediatric patients with relapsed/refractory ALL by retrospectively analyzing the diagnosis and treatment process of seven children with relapsed/refractory leukemia and observing the side effects of the two strategies and long-term survival.MethodsThe clinical features and treatment responses of patients aged <14 years with relapsed/refractory leukemia who received immunotherapy (including Chimeric Antigen Receptor T cell treatment and blinatumomab) at Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology between February 2014 and April 2022 were retrospectively analyzed.ResultsSeven children underwent immunotherapy. Five patients received immunotherapy and sequential allogeneic hematopoietic stem cell transplantation (HSCT), whereas the other two received only immunotherapy. Five patients achieved complete remission (71.4%). None of the patients had severe cytokine release syndrome. However, one developed grade 3 immune effector cell-associated neurotoxicity syndrome with prior leukoencephalopathy. The median follow-up period was 541 days (range, 186-3,180 days). No deaths were related to treatment. Three patients relapsed, two had CD19-negative recurrences, and the third showed CD19 antigen reduction. One patient died after disease progression, whereas the other died of HSCT-related complications. One patient abandoned the treatment after relapse and was lost to follow-up.ConclusionBlinatumomab and CAR T-cell therapy showed excellent remission rates and manageable toxicity in pediatric patients with relapsed/refractory leukemia. However, the duration of the remission was limited. Therefore, further prospective randomized clinical studies should be conducted to improve the long-term efficacy of immunotherapy.